Reversing the Paradigm: Protein Kinase C as a Tumor Suppressor. (May 2017) - Newton, Alexandra C.; Brognard, John
Abstract : The discovery in the 1980s that protein kinase C (PKC) is a receptor for the tumor-promoting phorbol esters fueled the dogma that PKC is an oncoprotein. Yet 30+ years of clinical trials for cancer using PKC inhibitors not only failed, but in some instances worsened patient outcome. The recent analysis of cancer-associated mutations, from diverse cancers and throughout the PKC family, revealed that PKC isozymes are generally inactivated in cancer, supporting a tumor suppressive function. In keeping with a bona fide tumor suppressive role, germline causal loss-of-function (LOF) mutations in one isozyme have recently been identified in lymphoproliferative disorders. Thus, strategies in cancer treatment should focus on restoring rather than inhibiting PKC. Trends: Functional characterization of somatic mutations in the protein kinase C (PKC) family of kinases reveals that a majority of mutations are loss of function (LOF) and no mutations are gain of function (GOF), reversing the paradigm that PKC isozymes are oncogenes. Germline LOF mutations in PKCδ are associated with cancer-like syndromes including lymphoproliferative disorders and juvenile systemic lupus erythematosus, further supporting the role of PKC isozymes as tumor suppressors. LOF mutant PKC isoforms act in a dominant-negative manner to suppress PKC signaling. These studies contribute to a larger theme in the field that many kinases will have tumor suppressive roles and inactivating mutations in kinases will be prevalent in cancer.